2020
DOI: 10.1021/acs.macromol.0c01318
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Crystallization in Butene-1/1,5-Hexadiene Copolymers: Mutual Effects of Molecular Factor and Flow Stimuli

Abstract: Polymorphism is determined by the intrinsic molecular architecture designed via chemical synthesis and the external flow stimuli applied in practical processing. In this work, flow-induced crystallization of butene-1/1,5-hexadiene random copolymers with 1.38–2.81 mol % cyclic methylene-1,3-cyclopentane (MCP) co-units was studied with the combination of in situ synchrotron wide-angle X-ray diffraction (WAXD) and an extensional rheometer. The results show that the incorporation of unique MCP co-units facilitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
(117 reference statements)
2
13
0
Order By: Relevance
“…Liu et al found that in butene-1/1,5-hexadiene copolymers, both tetragonal and trigonal phases were generated under quiescent crystallization, while the flow enhances the crystallization of form II more than that of form I′. 13 This is consistent with the flow-induced crystallization of form II in the butene/pentene copolymers studied in the present work. However, it is interesting to observe the flow-triggered occurrence of the II-I phase transition at the same temperature of form II formation in this work.…”
Section: Effect Of the Pentene Co-unit Concentrationsupporting
confidence: 90%
See 4 more Smart Citations
“…Liu et al found that in butene-1/1,5-hexadiene copolymers, both tetragonal and trigonal phases were generated under quiescent crystallization, while the flow enhances the crystallization of form II more than that of form I′. 13 This is consistent with the flow-induced crystallization of form II in the butene/pentene copolymers studied in the present work. However, it is interesting to observe the flow-triggered occurrence of the II-I phase transition at the same temperature of form II formation in this work.…”
Section: Effect Of the Pentene Co-unit Concentrationsupporting
confidence: 90%
“…43,44 The molecular weight and distribution were measured with gel permeation chromatography (PL-GPC 220) at 120 °C with trichlorobenzene as the eluent. The concentrations of pentene co-units in copolymers were determined using the hightemperature 13 C nuclear magnetic resonance. The molecular characteristics of polymers studied in this work are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations